2018
DOI: 10.1186/s13045-018-0561-0
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate shows potent anti-tumor activity in B-cell lymphoma

Abstract: BackgroundAlthough chemo-immunotherapy has led to an improved overall survival for most B-cell lymphoma types, relapsed and refractory disease remains a challenge. The malaria drug artesunate has previously been identified as a growth suppressor in some cancer types and was tested as a new treatment option in B-cell lymphoma.MethodsWe included artesunate in a cancer sensitivity drug screen in B lymphoma cell lines. The preclinical properties of artesunate was tested as single agent in vitro in 18 B-cell lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 49 publications
3
56
0
Order By: Relevance
“…It also exerts anti-tumor activities through the loss of mitochondrial membrane potential, Bcl-2 down-regulation, Bax up-regulation, and caspase-3 activation in human gastric cancer SGC-7901 and HGC-27, esophageal cancer Eca109 and Ec9706 cells, and breast cancer MCF-7 xenograft mice [673,681,683]. In addition, gene expression analysis identifies that ER stress is the most relevant pathway for the anti-tumor activity of artesunate in B-cell lymphoma [689]. Interestingly, artesunate selectively inhibits cell growth through iron-dependent and ROS-mediated ferroptosis in human head and neck cancer HN9 cells [690].…”
Section: Artesunatementioning
confidence: 99%
“…It also exerts anti-tumor activities through the loss of mitochondrial membrane potential, Bcl-2 down-regulation, Bax up-regulation, and caspase-3 activation in human gastric cancer SGC-7901 and HGC-27, esophageal cancer Eca109 and Ec9706 cells, and breast cancer MCF-7 xenograft mice [673,681,683]. In addition, gene expression analysis identifies that ER stress is the most relevant pathway for the anti-tumor activity of artesunate in B-cell lymphoma [689]. Interestingly, artesunate selectively inhibits cell growth through iron-dependent and ROS-mediated ferroptosis in human head and neck cancer HN9 cells [690].…”
Section: Artesunatementioning
confidence: 99%
“…These compounds, generally used for the treatment of malarial infections, have recently found additional use as antineoplastic agents 40,41 . Although the MoA is not fully understood, their cytotoxicity appears to rely on an iron/heme-dependent activation step and subsequent generation of Reactive Oxygen species (ROS) 42 .…”
Section: Genetic Screening Identifies Known and Novel Slc-drug Associmentioning
confidence: 99%
“…Furthermore, in recent years, several additional activities beyond anti-malarial activity have been observed [22,61]. In this respect, pre-clinical studies on artesunate have demonstrated anti-tumor activity against many different cancers including colon caancer [29], lung adenocarcinoma [31], pancreatic cancer [33], breast cancer [62] and different hematological malignancies [30,32,63]. The present study adds MCPyV-positive MCC to this list as we demonstrate the capability of artesunate to restrict growth of virus-positive MCC cells in vitro as well as in xenotransplantation mouse models in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that artesunate-induced death is not preceded by DNA fragmentation, a well-known characteristic of apoptosis [40]. Hence, apoptosis, a frequently described result of artesunate treatment in cancer cells [29][30][31]41], seems not to represent a crucial mechanism in these MCPyV-positive MCC cell lines. Only for MKL-2, no difference could be observed between the two dose response curves suggesting a possible contribution of apoptotic cell death.…”
Section: No Signs Of Apoptotic Cell Death Are Induced By Artesunate Imentioning
confidence: 96%
See 1 more Smart Citation